Handbook of research on computational forensics, digital crime, and investigation : methods and solutions - Li, Chang-Tsun. (Hershey, PA : Information Science Reference, 2010)
'This book provides a media for advancing research and the development of theory and practice of digital crime prevention and forensics, embracing a broad range of digital crime and forensics disciplines'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Computer crimes; Computer crimes -- Prevention; Forensic sciences; Computer security